A processing technology of graphite negative electrode material

By performing detailed raw material preparation, pretreatment, molding and graphitization in the graphite negative electrode material processing process, the problem of unrefined graphite treatment in the existing process is solved, and the quality and performance of the material are significantly improved, which is suitable for the application of high-performance lithium batteries.

CN119775008APending Publication Date: 2025-04-08CHINA MINMETALS GRP (HEILONGJIANG) GRAPHITE IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411664426.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing graphite negative electrode material processing technology has not been refined, resulting in the substances in the graphite central layer not participating in the reaction optimization, affecting the quality of the finished product.

Method used

A processing technology of graphite negative electrode material is adopted, including raw material preparation and mixing, pretreatment and granulation, molding processing, graphitization and sintering, surface treatment and storage. Specific steps include decomposition removal treatment, crushing and screening, isostatic pressure treatment, drying and grinding, graphitization treatment and surface treatment to improve the density, strength and purity of the graphite material.

Benefits of technology

Through the refined processing process, the quality of graphite negative electrode material is improved, its density, strength and purity are improved, the conductivity and charge and discharge performance are enhanced, thereby improving the overall performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775008A_ABST
    Figure CN119775008A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of graphite processing, and discloses a processing technology for graphite negative electrode material, comprising the following steps: S1, raw material preparation and mixing; S2, pretreatment and granulation; S3, molding processing; S4, graphitization and sintering; S5, surface treatment and storage; by adopting the processing technology of the invention, the treatment of natural graphite in the processing process is refined, and the quality of the finished product is improved under layer-by-layer treatment; by adopting the structural design of the invention, graphite is mixed with a modifier and an auxiliary agent to prepare a slurry, and then dried and ground together, under this treatment, the fusion between the several substances is tighter, and an ordered graphite crystal structure is formed, so that the performance of the finished graphite negative electrode material is better, which is helpful to improve the overall performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphite processing, and in particular relates to a processing technology for a graphite negative electrode material. Background Art

[0002] Graphite negative electrode material refers to the carbonaceous material used as the negative electrode of lithium-ion batteries. It has a layered structure and can accommodate the insertion and extraction of lithium ions. It has the characteristics of high specific energy, good stability, long cycle life, high reversible capacity, good electrical conductivity, and low lithium insertion voltage.

[0003] In the prior art, the patent with application number: 2023104557475 discloses a processing technology for graphite negative electrode materials, comprising the following steps: heating natural graphite at a temperature of 650-750°C for 3-4h, then adding concentrated sulfuric acid, potassium persulfate and sodium dodecylbenzene sulfonate to mix, reacting at a temperature of 180-200°C for 10-12h to obtain treated natural graphite; mixing the natural graphite treated in step (1) with asphalt, ball milling and mixing, granulating, and graphitizing and sintering at 2300-2500°C to obtain graphite negative electrode materials; wherein the mass ratio of the natural graphite treated in step (1) to asphalt is 1:0.18-0.22. The graphite negative electrode material prepared in the present application has good tap density, capacity and charge and discharge efficiency, and the preparation process is simple, energy consumption is low, and it is suitable for industrial production.

[0004] However, the graphite itself is not refined in the above steps, resulting in the possibility that the material in the central layer of the graphite does not participate in the reaction optimization, causing the quality of the finished graphite negative electrode material to be poor. Therefore, this application is based on process improvements to improve the quality of graphite negative electrode materials. Summary of the invention

[0005] In view of the problems raised by the above background technology, the purpose of the present invention is to provide a processing technology for graphite negative electrode materials.

[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:

[0007] A processing technology for graphite negative electrode material comprises the following steps:

[0008] S1. Raw material preparation and mixing:

[0009] S1.1, Select high-quality natural graphite for impurity removal;

[0010] S1.2, crush with a pulverizer, and then screen, the screened qualified graphite particle size is 10 ~ 50μm;

[0011] S1.3, mixing graphite powder with a modifier and an additive to prepare a slurry, and then subjecting the slurry to isostatic pressing;

[0012] S2. Pretreatment and granulation:

[0013] S2.1. Mix the slurry, asphalt and anhydrous ethanol in a ratio of 1:0.8:0.2 and stir for 1 to 2 hours, then let it stand for 10 to 30 minutes;

[0014] S2.2, sending the mixture obtained in step S2.1 into a high reaction kettle and introducing an inert gas to heat and dry;

[0015] S2.3, grinding with a jet mill, and then granulating with a pyrolysis device;

[0016] S2.4, use ball milling equipment to refine to obtain powder with a particle size of 10 to 20 μm;

[0017] S3, molding process:

[0018] S3.1, using a tablet press to press the powder into a plate-like material;

[0019] S3.2. Use a dryer to bake the plate-like material to dehydrate and harden it;

[0020] S4. Graphitization and sintering:

[0021] S4.1, placing the formed material into a high temperature furnace for graphitization treatment;

[0022] S4.2, obtaining a graphite material having negative electrode performance;

[0023] S5. Surface treatment and storage:

[0024] S5.1. Treating the surface of the graphite negative electrode material;

[0025] S5.2. Store in a ventilated, dry environment away from direct sunlight.

[0026] It is further defined that in step S1.1, the impurity removal treatment includes heating the graphite at high temperature to remove moisture and other volatile impurities therein, which helps to decompose some inorganic impurities and uses strong acids, strong alkalis and other chemical reagents to react with impurities in the graphite to generate water-soluble substances, which are then washed with water to achieve the purpose of purification, and utilizing the difference in floatability between graphite and impurity minerals to separate graphite from impurities through a flotation process to obtain a higher-grade graphite concentrate, thereby effectively improving the quality of the natural graphite serving as the basis.

[0027] It is further defined that in step S1.2, the crusher is selected to have a high dust absorption strength, and the areas of the crusher that will contact the graphite are all highly sealed, and solid guide rail oil is used in all places involving lubrication;

[0028] The high dust absorption strength pulverizer adopts high-efficiency filter material, which can effectively filter the dust generated in the graphite pulverization process, with high purification efficiency, ensuring a clean working environment. Through efficient dust removal, it can significantly reduce the damage of graphite dust to the respiratory system and skin of workers, protect the health of employees, reduce the occurrence of occupational diseases, reduce the emission of graphite dust into the atmosphere, effectively inhibit air pollution, protect the surrounding environment, ensure that emissions meet standards, and meet environmental protection requirements;

[0029] Sealing can effectively prevent graphite from entering the machine body and affecting the internal components, thereby affecting the service life of the pulverizer, and also effectively save and prevent the waste of graphite;

[0030] Solid guide rail oil will not drip, avoiding damage to graphite materials by oil stains and ensuring processing quality. Solid guide rail oil can form a stable high-strength oil film to protect equipment guides, reduce wear and improve processing accuracy. Guide rail oil has good lubrication effect, can reduce friction between equipment and workpieces, reduce equipment wear, and thus extend equipment service life. Solid guide rail oil can ensure smooth and vibration-free operation of equipment, reduce the occurrence of failures and improve processing efficiency.

[0031] It is further defined that in step S1.3, the modifier includes one or more of polyvinyl alcohol, carbon black and polyacrylic acid, and the auxiliary agent is N-methylpyrrolidone;

[0032] Polyvinyl alcohol as a modifier can enhance the bonding between graphite particles, reduce oxidation and mechanical wear, and help improve the electrical conductivity and charge and discharge performance of graphite;

[0033] As a modifier, carbon black can fill the micropores between graphite particles, increase the contact area between the electrolyte and the electrode, and enhance the ion transport and energy storage capacity of the electrode;

[0034] Polyacrylic acid as a modifier can make graphite particles disperse better, enhance the bonding force with other materials, and improve the conductivity and charge and discharge performance of graphite;

[0035] N-methylpyrrolidone (NMP) as an auxiliary agent can dissolve a variety of organic and inorganic substances, and has good solubility for polar and non-polar substances. It can effectively dissolve binders (such as PVDF), conductive materials, etc., so that the components are fully and evenly contacted. The toxicity of NMP is relatively low and it is less harmful to the human body. At the same time, it has a high flash point, is not easy to burn and explode, and is highly safe during storage, transportation and use. NMP has stable chemical properties and is not prone to decomposition, polymerization and other reactions. It can remain stable in the battery working environment to ensure product quality and performance. In addition, during the coating and baking stage, NMP evaporates from the wet film at a steady rate to form a porous microelectrode structure with uniform pore size and distribution, which helps to improve battery performance.

[0036] It is further defined that in step S1.3, the isostatic pressing treatment is carried out using an isostatic press or a warm isostatic press, and the isostatic pressing treatment is carried out for 0.5 to 2 hours under an environment of a pressure of 100 to 300 MPa and a temperature of 30 to 150°C, so as to ensure that the density, strength and purity of the graphite negative electrode material can be significantly improved, so that it has the characteristics of high strength, high density, high purity, high chemical stability, high thermal conductivity and electrical conductivity, high temperature resistance, radiation resistance, strong lubricity and easy processing, and through isostatic pressing treatment, the graphite negative electrode material can obtain isotropic properties, that is, the performance of the material is independent of size, shape, and sampling direction, which helps to improve the overall performance of the battery.

[0037] It is further defined that in step S2.2, the drying temperature is 150-250°C and the working pressure of the high reactor is 2.5kg to ensure the drying effect.

[0038] It is further defined that in step S2.3, the particle size range of the pyrolysis equipment is 10 to 30 μm, which reduces the working pressure of the subsequent ball milling equipment and ensures that the particle size produced meets the requirements.

[0039] It is further defined that in step S3.2, the baking temperature is 150-250°C to ensure the drying effect.

[0040] It is further defined that in step S4.1, the temperature of the graphitization treatment is increased in stages, the temperature of the first stage is 1000-1800°C, the treatment is 1-2h, and the temperature of the second stage is 1800-3000°C, the treatment is 2-4h. As the temperature gradually increases, the distance between graphite layers gradually becomes smaller, the structure gradually improves, and an ordered graphite crystal structure is formed, thereby improving the volume density, electrical conductivity, thermal conductivity and other properties of the material. In addition, the staged temperature increase helps the non-graphite carbon to gradually transform into graphite carbon with a three-dimensional regular and ordered structure of graphite, thereby improving the lubrication and corrosion resistance of the material, and better applying it to batteries. Although graphitization is a high energy consumption link, the staged temperature increase can more effectively utilize energy, reduce production costs, and improve production efficiency.

[0041] It is further defined that in step S5.1, the surface treatment includes one or more of grinding and polishing for deburring, pickling, coating with polymer coating, coating with phenolic resin and introducing phosphorus element modification and ion implantation;

[0042] Grinding, polishing, deburring and pickling make the surface of graphite material uniform. If the graphite surface is uneven, it is difficult to form a uniform and dense SEI film.

[0043] Coating with polymer coating, encapsulating with phenolic resin and introducing phosphorus element modification can significantly enhance the corrosion resistance of graphite anode materials, thereby extending their service life;

[0044] Ion implantation changes the chemical composition of graphite by introducing foreign atoms, thereby significantly improving the strength and hardness of graphite parts, enhancing their tensile strength and resistance to hardness deformation, and repairing micro-defects and cracks on the surface of graphite parts, improving surface smoothness, while increasing surface hardness and wear resistance, reducing wear and friction, and extending service life. Ion implantation can also form a metal oxide barrier, slow down the high-temperature oxidation process, and further extend the service life of graphite parts. It can also effectively adjust the chemical structure of the graphite material surface, thereby improving its performance, such as transforming the hybrid structure of carbon atoms and improving bonding and tribological properties.

[0045] The beneficial effects of the present invention are as follows:

[0046] The processing technology of the present invention is adopted to refine the processing of natural graphite during the processing, and the quality of the finished product is improved through layer-by-layer processing;

[0047] By adopting the structural design of the present invention, graphite is mixed with a modifier and an auxiliary agent to prepare a slurry, which is then dried and ground together. Under this treatment, the fusion between the several substances is tighter, forming an ordered graphite crystal structure, so that the performance of the finished graphite negative electrode material is better, which in turn helps to improve the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The present invention can be further illustrated by the non-limiting examples given in the accompanying drawings;

[0049] Figure 1 A schematic flow chart of a processing technology embodiment of a graphite negative electrode material of the present invention; DETAILED DESCRIPTION

[0050] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0051] like Figure 1 As shown, a processing technology of a graphite negative electrode material of the present invention comprises the following steps:

[0052] S1. Raw material preparation and mixing:

[0053] S1.1, Select high-quality natural graphite for impurity removal;

[0054] S1.2, crush with a pulverizer, and then screen, the screened qualified graphite particle size is 10 ~ 50μm;

[0055] S1.3, mixing graphite powder with a modifier and an additive to prepare a slurry, and then subjecting the slurry to isostatic pressing;

[0056] S2. Pretreatment and granulation:

[0057] S2.1. Mix the slurry, asphalt and anhydrous ethanol in a ratio of 1:0.8:0.2 and stir for 1 to 2 hours, then let it stand for 10 to 30 minutes;

[0058] S2.2, sending the mixture obtained in step S2.1 into a high reaction kettle and introducing an inert gas to heat and dry;

[0059] S2.3, grinding with a jet mill, and then granulating with a pyrolysis device;

[0060] S2.4, use ball milling equipment to refine to obtain powder with a particle size of 10 to 20 μm;

[0061] S3, molding process:

[0062] S3.1, using a tablet press to press the powder into a plate-like material;

[0063] S3.2. Use a dryer to bake the plate-like material to dehydrate and harden it;

[0064] S4. Graphitization and sintering:

[0065] S4.1, placing the formed material into a high temperature furnace for graphitization treatment;

[0066] S4.2, obtaining a graphite material having negative electrode performance;

[0067] S5. Surface treatment and storage:

[0068] S5.1. Treating the surface of the graphite negative electrode material;

[0069] S5.2. Store in a ventilated, dry environment away from direct sunlight.

[0070] In step S1.1, the impurity removal treatment includes heating the graphite at high temperature and using chemical reagents such as strong acid and strong alkali to react with impurities in the graphite and utilizing the difference in floatability between graphite and impurity minerals.

[0071] In step S1.2, the crusher is selected to have high dust absorption strength, and the areas of the crusher that will contact the graphite are all highly sealed, and solid guide rail oil is used in all places involving lubrication;

[0072] In step S1.3, the modifier includes one or more of polyvinyl alcohol, carbon black and polyacrylic acid, and the auxiliary agent is N-methylpyrrolidone;

[0073] In step S1.3, the isostatic pressing treatment is performed using an isostatic press or a warm isostatic press, and the isostatic pressing treatment is performed for 0.5 to 2 hours under an environment of a pressure of 100 to 300 MPa and a temperature of 30 to 150° C.;

[0074] In step S2.2, the drying temperature is 150-250°C, and the working pressure of the high reaction kettle is 2.5 kg;

[0075] In step S2.3, the particle size range of the pyrolysis equipment is 10 to 30 μm;

[0076] In step S3.2, the baking temperature is 150-250°C;

[0077] In step S4.1, the temperature of the graphitization treatment is increased in stages, the temperature of the first stage is 1000-1800°C, the treatment time is 1-2h, and the temperature of the second stage is 1800-3000°C, the treatment time is 2-4h;

[0078] In step S5.1, the surface treatment includes one or more of grinding and polishing to remove burrs, pickling, coating with polymer coating, coating with phenolic resin and introducing phosphorus element modification and ion implantation;

[0079] In this implementation case, high-quality natural graphite raw materials are selected, and then high-temperature heating is used to remove moisture and other volatile impurities therein, which helps to decompose some inorganic impurities. Then, chemical reagents such as strong acids and strong alkalis are used to react with impurities in the graphite to generate water-soluble substances, which are then washed with water to achieve the purpose of purification. Finally, the difference in floatability between graphite and impurity minerals is used to separate graphite from impurities through a flotation process to obtain a high-grade graphite concentrate, which effectively improves the quality of the natural graphite as the basis. Under the treatment of these three processes, high-quality graphite raw materials are obtained;

[0080] The raw material is then crushed using a crusher with high dust absorption strength. Before crushing, the crusher is inspected for sealing. After the raw material is crushed, it is screened to obtain graphite powder with a particle size of 10 to 50 μm. The graphite powder that is not within this range is returned to the crusher for secondary crushing until the crushing is completed.

[0081] The graphite powder that meets the requirements is mixed with polyvinyl alcohol, carbon black and polyacrylic acid as modifiers and N-methylpyrrolidone as an auxiliary agent to obtain a slurry. In this process, the powdered graphite can be completely combined with polyvinyl alcohol, carbon black, polyacrylic acid and N-methylpyrrolidone to ensure its conductivity, ion transmission, energy storage and charge and discharge performance. Then, a warm isostatic press is used for isostatic pressing to significantly improve the density, strength and purity of the graphite, so that it has the characteristics of high strength, high density, high purity, high chemical stability, high thermal conductivity and electrical conductivity, high temperature resistance, radiation resistance, strong lubricity and easy processing. The refined processing of this step is superior to most of the public technologies in the prior art, and thus superior to the quality of its finished product;

[0082] The slurry was mixed with asphalt and anhydrous ethanol in a ratio of 1:0.8:0.2 for 2 hours, and then allowed to stand for 25 minutes. After the shape was basically fixed, it was placed in a high-speed reactor and completely dried at a working pressure of 2.5 kg and a drying temperature of 200°C. During the drying process, inert gas was introduced to protect the slurry to prevent its internal structure from changing due to temperature, thereby ensuring the quality of the subsequent finished product.

[0083] The completely dried slurry is ground with a jet mill, and the particle size requirement of the ground powder is not high. Then, a pyrolysis device is used for granulation to obtain graphite particles with a particle size range of 10 to 30 μm. The graphite particles are refined with a ball mill to obtain a target powder with a particle size of 10 to 20 μm.

[0084] The powder is made into a plate-shaped material using a tablet press. It should be noted that according to the performance of the tablet press, the divided material can be directly pressed into the required cylindrical material or rod-shaped material. Pressing the material into a plate-shaped material is conducive to subsequent forming and cutting. After forming, the material is dried and hardened at a temperature of 200°C;

[0085] Then the hardened material is placed in a high-temperature furnace for graphitization treatment. The treatment temperature is divided into two stages. First, it is treated at a temperature of 1500°C for 2 hours, and then the temperature is slowly raised to 2500°C for 3 hours to obtain a graphite material with negative electrode performance, thereby completing the processing purpose;

[0086] Subsequent surface treatment of the finished product, including but not limited to grinding and polishing to remove burrs, pickling, coating with polymer coating, coating with phenolic resin and introducing phosphorus element modification and ion implantation, shall be considered according to specific use requirements. After treatment, it shall be stored in a ventilated, dry environment without direct sunlight. The storage method can also be selected according to the specific environment;

[0087] The performance data of three groups of graphite negative electrode materials sampled and processed using the process of this embodiment and the performance data of three groups of graphite negative electrode materials purchased on the market are compared as follows:

[0088]

[0089]

[0090] In summary, the graphite negative electrode material processed by this process is significantly better than the graphite negative electrode material purchased on the market in terms of tap density, charge specific capacity, discharge specific capacity and charge and discharge efficiency. Therefore, the graphite negative electrode material processed by this process will have better comprehensive performance when subsequently used in lithium batteries.

[0091] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.

Claims

1. A processing technology for graphite negative electrode material, characterized in that: The steps include: S1. Raw material preparation and mixing: S1.1, Select high-quality natural graphite for impurity removal; S1.2, crush with a pulverizer, and then screen, the screened qualified graphite particle size is 10 ~ 50μm; S1.3, mixing graphite powder with a modifier and an additive to prepare a slurry, and then subjecting the slurry to isostatic pressing; S2. Pretreatment and granulation: S2.

1. Mix the slurry, asphalt and anhydrous ethanol in a ratio of 1:0.8:0.2 and stir for 1 to 2 hours, then let it stand for 10 to 30 minutes; S2.2, sending the mixture obtained in step S2.1 into a high reaction kettle and introducing an inert gas to heat and dry; S2.3, grinding with a jet mill, and then granulating with a pyrolysis device; S2.4, use ball milling equipment to refine to obtain powder with a particle size of 10 to 20 μm; S3, molding process: S3.1, using a tablet press to press the powder into a plate-like material; S3.

2. Use a dryer to bake the plate-like material to dehydrate and harden it; S4. Graphitization and sintering: S4.1, placing the formed material into a high temperature furnace for graphitization treatment; S4.2, obtaining a graphite material having negative electrode performance; S5. Surface treatment and storage: S5.

1. Treating the surface of the graphite negative electrode material; S5.

2. Store in a ventilated, dry environment away from direct sunlight.

2. The processing technology of a graphite negative electrode material according to claim 1, characterized in that: In step S1.1, the impurity removal treatment includes heating the graphite at high temperature and using chemical reagents such as strong acid and strong alkali to react with impurities in the graphite and utilizing the difference in floatability between graphite and impurity minerals.

3. The processing technology of a graphite negative electrode material according to claim 1, characterized in that: In step S1.2, the crusher is selected to have high dust absorption strength, and all areas of the crusher that come into contact with graphite are highly sealed, and all places involving lubrication use solid guide rail oil.

4. The processing technology of a graphite negative electrode material according to claim 1, characterized in that: In step S1.3, the modifier includes one or more of polyvinyl alcohol, carbon black and polyacrylic acid, and the auxiliary agent is N-methylpyrrolidone.

5. The processing technology of a graphite negative electrode material according to claim 1, characterized in that: In step S1.3, the isostatic pressing treatment is performed using an isostatic press or a warm isostatic press, and the isostatic pressing treatment is performed for 0.5 to 2 hours under an environment of a pressure of 100 to 300 MPa and a temperature of 30 to 150°C.

6. The processing technology of a graphite negative electrode material according to claim 1, characterized in that: In step S2.2, the drying temperature is 150-250°C, and the working pressure of the high reactor is 2.5 kg.

7. The processing technology of a graphite negative electrode material according to claim 1, characterized in that: In step S2.3, the particle size range of the pyrolysis equipment is 10 to 30 μm.

8. The processing technology of a graphite negative electrode material according to claim 1, characterized in that: In step S3.2, the baking temperature is 150-250°C.

9. The processing technology of a graphite negative electrode material according to claim 1, characterized in that: In step S4.1, the temperature of the graphitization treatment is increased in stages. The temperature of the first stage is 1000-1800°C for 1-2 hours, and the temperature of the second stage is 1800-3000°C for 2-4 hours.

10. The processing technology of a graphite negative electrode material according to claim 1, characterized in that: In step S5.1, the surface treatment includes one or more of grinding and polishing for deburring, pickling, coating with polymer coating, coating with phenolic resin and introducing phosphorus element modification and ion implantation.